Analysis of Factors Influencing Organisational Citizenship Behaviour of Employees of Airport Organizing Unit Class 1 Mopah Merauke - Rizal, Fathu; Ratang, Westim; Sultan, Zulkifli (East Asian Journal of Multidisciplinary Research, 2024)
The Airport Organizing Unit requires reliable apparatus resources, both in terms of ability in their work and behavior in the organization, because apparatus resources are an important element in the context of providing public services. This research aims to analyze the influence of organizational climate, work environment and supervision in motivating employees to form organizational citizenship behavior among Aviation Security Section employees at the UPBU Class 1 Mopah Merauke Office. Data was collected from all Aviation Security Section employees at the UPBU Class 1 Mopah Merauke Office through a questionnaire. A saturated sampling technique was carried out with a total final sample of 94 respondents. The data collected was analyzed using the SEM (Structural Equation Modeling) technique. The results of the analysis show that there is an influence of organizational climate, work environment and supervision in motivating employee work, but this influence has no effect on organizational citizenship behavior. Thus, work motivation cannot explain the mediating role in this relationship